2021
DOI: 10.1109/tem.2019.2914995
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Management in Process Industries: The Impact of Market Conditions and Capital Expenditure on Firm Performance

Abstract: Process industries operate in commodity markets with low product variety, little product differentiation, and highly capital-intensive manufacturing. Because prices are volatile and demand is uncertain, manufacturing capabilities become the main strategic competitive lever. The purpose of this paper is to evaluate the interplay between market conditions, capital expenditure, manufacturing flexibility, and production capacity to effectively analyze the consequences of manufacturing investments in both the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 88 publications
(106 reference statements)
2
8
0
Order By: Relevance
“…Specifically, our study analyzes big capitalization companies and proves that capital expenditure impacts long-term performance, with no proof of any impact in the short term. The results of this study contribute to the discussion regarding the inconsistent results of previous studies in which capital expenditure was found to have both a short-term effect (Ball et al, 2009;Kim, 2001;Turner & Hesford, 2019) and a long-term effect (Canace et al, 2018;Chen & Chang, 2020;Kothari et al, 2002;Moser et al, 2021) on company performance.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Specifically, our study analyzes big capitalization companies and proves that capital expenditure impacts long-term performance, with no proof of any impact in the short term. The results of this study contribute to the discussion regarding the inconsistent results of previous studies in which capital expenditure was found to have both a short-term effect (Ball et al, 2009;Kim, 2001;Turner & Hesford, 2019) and a long-term effect (Canace et al, 2018;Chen & Chang, 2020;Kothari et al, 2002;Moser et al, 2021) on company performance.…”
Section: Discussionmentioning
confidence: 49%
“…This signal will arguably result in the short-term and external-based measurements of firm performance, as in most previous studies. The external-based measurement of firm performance refers to market value (Kim et al, 2021;Moser et al, 2021) and market or investor responses (Akbar et al, 2008;Burton, 2005;Chen & Chang, 2020;Juniarti & Toly, 2021). This study complements previous studies by using fundamental measurements (ROA and ROE) to confirm the influence of capital expenditure on long-term firm performance.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Many studies also analysed the effect of contextual factors (Marin-Garcia and Bonavia, 2015;Shah and Ward, 2003) or the inter-relationship between different lean practices (Fullerton et al, 2014). However, none of them considered capital investment, although it is usually a crucial aspect in process industries (Moser et al, 2019). Although lean does not rely on big investments to improve performance, still, it can help to enhance its impact.…”
Section: The Lean Practices-performance Relationshipmentioning
confidence: 99%
“…The Volvo case (Netland and Ferdows, 2016) is a good example of this. Furthermore, the process industry has some specifics, like capital intensity or a low variety of non-discrete products (Moser et al, 2019), that make lean programs, and the portfolio of relevant lean practices different. Therefore, the following research questions will be answered: RQ1.…”
Section: The Research Questionsmentioning
confidence: 99%